Educational support to the inclusion of student with autism spectrum disorder: educational service specialized in the view of teachers - Pinto, Rosana Zela (2022)
This study aimed to verify which are the pedagogical strategies used in the common teaching and in the specialized educational attendance for a student with autism spectrum disorder (ASD). The research method was descriptive, with the application of two questionnaires, with qualitative data analysis. The study participants were three teachers, two from ordinary education and one from specialized education. The questionnaires were applied after the research was approved by the ethics committee. The results indicated that all teachers understood inclusive education as a way of providing all students with learning in a common environment, with conviviality and interaction with other colleagues. With regard to the interaction of regular education teachers with the professional of specialized care, the teachers stressed that together they seek ways to better pass on school content to students with ASD, in addition to understanding that, in relation to collaborative work, there are many challenges as the anticipation of contents to think teaching strategies that favor everyone. Thus, it can be seen that the inclusion theme is hard work and that many educators are still unable to identify and understand that students learn differently and at different times.